Oropharyngeal cancer is no longer a disease of younger patients and the prognostic advantage of Human Papillomavirus is attenuated among older patients: Analysis of the National Cancer Database. (August 2018) - Rettig, Eleni M.; Zaidi, Munfarid; Faraji, Farhoud; Eisele, David W.; El Asmar, Margueritta; Fung, Nicholas; D'Souza, Gypsyamber; Fakhry, Carole
Highlights: The mean age of oropharyngeal cancer (OPC) diagnosis is increasing significantly. Age at diagnosis is increasing similarly for HPV-positive and HPV-negative OPCs. The proportion of OPCs that are HPV-positive is increasing for all age groups. The survival advantage of HPV-positive tumors is attenuated in older patients. We identify a growing elderly population of HPV-OPC patients with reduced survival. Abstract: Objectives: HPV-positive oropharyngeal cancer (OPC) patients have been observed to be younger than patients with HPV-negative OPC at diagnosis. We evaluated recent trends in age at OPC diagnosis, and whether older age attenuates the survival benefit of HPV-positive tumor status. Materials and methods: Patients diagnosed with OPC from 2004 to 2014 represented in the National Cancer Database were included. HPV tumor status was available after 2010. Trends in age by calendar year were compared using linear regression. Overall survival was compared using Cox Proportional Hazards models. Results: The mean age of OPC patients (N = 119, 611) increased significantly from 2004 to 2014 (ß = 0.21 years of age per calendar year, 95% confidence interval [CI] = 0.19–0.23). The increase in age from 2010 to 2014 was similar for HPV-positive (N = 21, 880; ß = 0.63, 95%CI = 0.53–0.72) and HPV-negative (N = 11, 504; ß = 0.59, 95%CI = 0.45–0.74) patients. Between 2010 and 2014, the proportion of OPCs that were HPV-positive increased significantly for all age groups, including for patients ≥70 years old (from 45% to 60%, ptrend < 0.001). Although patients ≥70 years with HPV-OPC had improved survival compared to those with HPV-negative OPC (adjusted hazard ratio [aHR] = 0.65, 95%CI = 0.55–0.76), the survival benefit of HPV-positive tumor status was significantly attenuated compared to younger HPV-OPC patients (50–59 years: aHR = 0.45, 95%CI = 0.39–0.51; pinteraction < 0.001). Conclusion: The age at OPC diagnosis is increasing for both HPV-positive and HPV-negative patients, and a rising proportion of older patients have HPV-positive tumors. These findings dispel the notion that HPV-positive OPC is a disease of younger patients, identify a growing elderly population of HPV-positive OPC patients with reduced survival, and have implications for evolving treatment paradigms.